2002
DOI: 10.1177/107602960200800106
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement of Complete Compression Ultrasound for Clinically Suspected Deep Vein Thrombosis

Abstract: The interobserver variability of compression ultrasound of proximal and distal veins in clinically suspected deep vein thrombosis was assessed. One hundred one symptomatic legs of all patients referred for clinically suspected deep vein thrombosis on 21 consecutive workdays were examined by two investigators independently according to a standardized protocol of complete compression ultrasound (CCUS) with 28 predefined venous segments between groin and ankle. Incompressible vein segments were defined as thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 29 publications
1
38
0
1
Order By: Relevance
“…CCUS is accurate in patients with symptomatic DVT. 25 Thus, for the purposes of the present study, we converted the validated venographic surrogate measure to ultrasound using a standardized examination protocol (CCUS) that was validated internally 18 and externally 26 in previous studies. We also designed a scoring system that closely resembled the venographic Marder score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCUS is accurate in patients with symptomatic DVT. 25 Thus, for the purposes of the present study, we converted the validated venographic surrogate measure to ultrasound using a standardized examination protocol (CCUS) that was validated internally 18 and externally 26 in previous studies. We also designed a scoring system that closely resembled the venographic Marder score.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, high interobserver agreement existed in identifying affected proximal and distal venous segments in symptomatic patients (ϭ1.0 and ϭ0.90, respectively) with this CCUS protocol. 18 The score for each affected venous segment (except for the deep femoral) was adjusted for thrombus diameter (assessed under full compression and compared with the diameter of the corresponding artery). The segment score was increased 1.5-fold if its compressed diameter was Ն1.5 times the arterial diameter and reduced 0.5-fold if this was Յ0.5 times the arterial diameter.…”
Section: Scoring Of Ccus and Perfusion Lung Scan Examinationsmentioning
confidence: 99%
“…According to our hospital guidelines, all patients with clinical suspicion of DVT underwent immediate (within 24 h) bilateral complete compression ultrasound (CCUS) in our vascular unit by vascular specialists experienced in compression ultrasound using a standardized CCUS protocol [19,20]. Proximal DVT was defined as any DVT occurring in a vein of the deep vein system of the lower extremity at the level of the popliteal vein or above.…”
Section: Efficacy Endpointsmentioning
confidence: 99%
“…In terms of the discrepancy between the two US reports, this could have been due to interrater reliability; however, it has been shown that with experienced observers, interobserver reliability for lower extremity DVT is excellent, at 94%. 12 It is unclear why the second sonogram was negative; however, it does not change the fact that there was a previous positive sonogram. This patient had a posttest probability of DVT greater than 90% after the initial positive sonogram, suggesting that he should have been maintained on the appropriate dose and duration of anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%